Art Cities, Cultural Districts and Museums - Lazzeretti, Luciana (Firenze University Press, 2004)
The subject of economic valorisation has become a current topic and the idea that culture can be considered a factor of economic production, able to generate wealth, appears to have been generally accepted. The book consists of a series of essays about the economic valorisation of the cultural, artistic and environmental heritage of the art city of Florence using a business economics approach and will appeal to scholars and researchers focusing on the cultural economics and managerial economics of art and to practitioners in the cultural sector and policy makers.p‰The subject of economic valorisation has become a current topic and the idea that culture can be considered a factor of economic production, able to generate wealth, appears to have been generally accepted. The book consists of a series of essays about the economic valorisation of the cultural, artistic and environmental heritage of the art city of Florence using a business economics approach and will appeal to scholars and researchers focusing on the cultural economics and managerial economics of art and to practitioners in the cultural sector and policy makers.